2015
DOI: 10.12688/f1000research.6522.2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced and Conventional Magnetic Resonance Imaging in Neuropsychiatric Lupus

Abstract: Neuropsychiatric lupus is a major diagnostic challenge, and a main cause of morbidity and mortality in patients with systemic lupus erythematosus (SLE). Magnetic resonance imaging (MRI) is, by far, the main tool for assessing the brain in this disease. Conventional and advanced MRI techniques are used to help establishing the diagnosis, to rule out alternative diagnoses, and recently, to monitor the evolution of the disease. This review explores the neuroimaging findings in SLE, including the recent advances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 86 publications
(142 reference statements)
0
28
0
3
Order By: Relevance
“…It is crucial to differentiate NPSLE from SLE without neurologic or psychiatric symptoms (named non‐NPSLE; Sarbu et al, ). However, the discrimination of NPSLE from non‐NPSLE is difficult in a clinical setting, requiring stable and reliable biological and radiographical markers (Castellino, Govoni, Giacuzzo, & Trotta, ; Cervera et al, ; Sarbu, Bargalló, & Cervera, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to differentiate NPSLE from SLE without neurologic or psychiatric symptoms (named non‐NPSLE; Sarbu et al, ). However, the discrimination of NPSLE from non‐NPSLE is difficult in a clinical setting, requiring stable and reliable biological and radiographical markers (Castellino, Govoni, Giacuzzo, & Trotta, ; Cervera et al, ; Sarbu, Bargalló, & Cervera, ).…”
Section: Introductionmentioning
confidence: 99%
“…WML occur in 40-60% of NPSLE patients, even at the earliest stages of the disease. [30][31][32][33] The known risk factors for WML in NPSLE include age, duration of NP symptoms and total cumulated steroid dose, 34 and total WML volume correlates with disease activity measured with SLEDAI score and Damage Index. It has even been suggested that WML may serve as a predictive factor, useful for monitoring disease progression and response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been suggested that WML may serve as a predictive factor, useful for monitoring disease progression and response to therapy. 33,34 However, WML identification and even quantitative description has poor discriminative value for MS and SLE, mainly because of its non-specific character and a variety of confounding factors (i.e. coexistence of other diseases that cause WM pathology, such as hypertension or atherosclerosis).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to the presence of WMH on MRI, including age, hypertension, diabetes mellitus and dyslipidaemia. 29 In patients with SLE, WMH may occur in the absence of NPSLE. However, in patients with NPSLE, age, duration of neuropsychiatric manifestations and cumulative steroid dosage are independent predictors of WMH.…”
Section: Mri Findings In Patients With Npslementioning
confidence: 99%